Understanding the Potential Role and Delivery Approaches of Nitric Oxide in Chronic Wound Healing Management - Kandhwal, Mimansa; Behl, Tapan; Kumar, Arun; Arora, Sandeep (Current Pharmaceutical Design, 2021)
Nitric oxide (NO) is a promising pharmaceutical component that has vasodilator, anti-bacterial, and wound healing activities. Chronic ulcers are non-healing disorders that are generally associated with distortion of lower limbs. Among the severe consequence derivatives of these diseases are the problems of chronic wound progression. NO, which is categorized as the smallest gaseous neurotransmitter, has beneficial effects in different phases of chronic inflammation. The defensive mechanism of NO is found useful in several severe conditions, such as gestational healing, gastrointestinal healing, and diabetic healing. The current review presents an updated collection of literature about the role of NO in chronic ulcers due to the prevalence of diabetes, DPN, and diabetic foot ulcers, and because of the lack of available effective treatments to directly address the pathology contributing to these conditions, novel treatments are being sought. This review also collects information about deficiency of NO synthase in diabetic patients, leading to a lack of vascularization of the peripheral nerves, which causes diabetic neuropathy, and this could be treated with vasodilators such as nitric oxide. Apart from the pharmacological mechanism of NO, the article also reviewed and analyzed to elucidate the potential of transdermal delivery of NO for the treatment of chronic ulcers.
Keywords: Nitric oxide